No Association between Thrombin Generation and Intra-Plaque Haemorrhage in Symptomatic Carotid Atherosclerotic Plaques: The Plaque at RISK (PARISK) Study - Crombag, Geneviève A. J. C.; Spronk, Henri M.; Nelemans, Patty; Schreuder, Floris H. B. M.; Truijman, Martine T. B.; van Dijk, Anouk C.; de Rotte, Alexandra A. J.; Liem, Madieke I.; Daemen, Mat J. A. P.; van der Steen, Anton F. W.; Mess, Werner H.; Nederkoorn, Paul J.; Hendrikse, Jeroen; van der Lugt, Aad; Wildberger, Joachim E.; ten Cate, Hugo; van Oostenbrugge, Robert J.; Kooi, M. Eline (Thrombosis and Haemostasis, 2018)
Background Carotid atherosclerosis is an important cause of stroke. Intra-plaque haemorrhage (IPH) on magnetic resonance imaging (MRI) increases stroke risk. Development of IPH is only partly understood. Thrombin is an essential enzyme in haemostasis. Experimental animal studies have shown conflicting results on the relation between thrombin and plaque vulnerability. We hypothesize that decreased thrombin generation (TG) is associated with IPH and plaque vulnerability.Objective This article investigates whether TG is associated with IPH and other features of plaque vulnerability in stroke patients.Methods Recently symptomatic stroke patients underwent carotid MRI and blood sampling. MRI plaque features include plaque burden, presence of IPH, amount of lipid-rich necrotic core (LRNC), calcified tissue and fibrous tissue (% of total wall volume). TG was assessed in platelet-poor plasma and expressed as: peak height (PH) and endogenous thrombin potential (ETP). MR images could be analysed in 224 patients. Blood samples were available in 161 of 224 patients. Binary multivariate logistic and linear regression were used to investigate the association between TG and MRI plaque features.Results IPH and LRNC were present in 65 (40%) and 102 (63%) of plaques. There were no significant associations between TG and IPH; PH odds ratio (OR) = 1, 95% confidence interval (CI): 0.76 to 1.45 and ETP OR = 1, 95% CI: 0.73 to 1.37. After correction for age, sex and hypercholesterolaemia, the association was weak but non-significant; PH: OR = 0.76, 95% CI: 0.52 to 1.10 and ETP: OR = 0.73, 95% CI: 0.53 to 1.37.Conclusion Features of carotid plaque on MRI show no significant association with TG in stroke patients. Systemic TG does not seem to be an important factor in IPH development.
Keywords: carotid stenosis; ischaemic attack; transient; magnetic resonance imaging; stroke; thrombin